Bifunctional oxygen electrodes of homogeneous Co4N nanocrystals@N-doped carbon hybrids for rechargeable Zn-air batteries. (October 2019) - Chen, Lulu; Zhang, Yelong; Liu, Xiangjian; Long, Ling; Wang, Siyu; Xu, Xiaolong; Liu, Minchao; Yang, Wenxiu; Jia, Jianbo
Abstract: The development of transition metal nitrides/carbon hybrids with well-organized morphology, outstanding efficiency and durability for Zn-air batteries are of great urgency. Herein, a morphology-controlled strategy to efficiently fabricate uniform Co4 N nanoparticles anchored on N -doped carbon (Co4 N@NC-m) is reported. The diameters and distribution of Co4 N nanocrystals can be tuned to be homogeneous profited by abundant N sources in melamine. Moreover, thanks to the advantages of higher nitrogen doping content, better electrical conductivity, higher degree of graphitization, and larger electrochemical surface area, Co4 N@NC-m possesses excellent oxygen reduction reaction (half-wave potential of 0.87 V) and oxygen evolution reaction (overpotential of 398 mV at 10 mA cm −2 ) activities in basic solution. The Zn-air battery fabricated with Co4 N@NC-m owns higher open circuit voltage (1.490 V), larger power density, and better rechargeability than those of the commercial IrO2  + 20% Pt/C catalysts, which proves the potential application in practical energy conversion devices. Graphical abstract: A novel strategy was proposed to design morphology-controlled Co4 N nanocrystals deposited on N -doped carbon as high-efficient and durable air cathode catalysts for rechargeable Zn-air batteries, which provides new thoughts for developing non-noble metal catalysts for clean energy conversion devices.Image 1